Threshold Group Signature Scheme with Privilege Subjects Based on ECC - Xueming Wang; Yurong Dong (2010 International Conference on Communications and Intelligence Information Security, 2010)
This paper analyzes and studies of a threshold group signature scheme which is based on ElGamal type. In order to overcome the shortcomings of the scheme, a new threshold group signature scheme with privilege subjects based on ECC is proposed. The new scheme is able to prevent the fraud of key distribution center effectively. Only when the scheme satisfies (t, n) and (t 1 , n 1 ) threshold signature, can the valid signature be generated. Thus the scheme reached the property of threshold. The program also satisfies the properties of anonymity, unforgeability, trace ability, reversibility and it can resist collusion attacks too.